2022
DOI: 10.1002/ijgo.14529
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with puerperal women's perception of the support received from their companions during labor and delivery

Abstract: In 2018, the World Health Organization (WHO) launched a set of intrapartum care recommendations for a positive birth experience through a holistic and human rights-based approach. These recommendations are considered a model of health care during childbirth that considers the complexity and heterogeneity of healthcare systems and practices, reducing unnecessary interventions during labor and delivery. 1 Women's perception of empowerment for childbirth may result from a positive experience influenced by the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
1
1
Order By: Relevance
“…Our study did not show a significant association between marital status and QoL. However, the partner's support is essential for the experience of a meaningful maternity process, whether by improving the QoL during pregnancy or even during delivery 17 …”
Section: Discussioncontrasting
confidence: 81%
“…Our study did not show a significant association between marital status and QoL. However, the partner's support is essential for the experience of a meaningful maternity process, whether by improving the QoL during pregnancy or even during delivery 17 …”
Section: Discussioncontrasting
confidence: 81%
“…Results showed that the women in the intervention group had higher satisfaction with childbirth [ 27 ]. Findings from this study revealed that the empowerment of the companion during labor and delivery made a positive difference on the woman’s perception of support [ 28 ]. Therefore, we recommend that companions are guided on admission to help them settle into this very significant role to positively impact women’s experience of care.…”
Section: Discussionmentioning
confidence: 99%